The brain–the organ of the psychic (The lesions / the defense mechanisms) - Rotarescu, V (Carol Davila University Press, 2010)

(untitled)
The article is based on the Leopold Szondi theory (March 11, 1893 – January 24, 1986), who was a Hungarian psychiatrist. He is known for the psychological tool that bears his name, the Szondi test. He developed a form of depth psychology that had some prominence in Europe in the mid–20th century, but has been ignored for the most part), the study seeks to correlate the szondian test results with the imagistic ones on a wide–range pathology. In the Neurosurgery Department, patients are investigated using modern exploration methods (MRI, CTscan, and computed EEG, etc.) in order to identify possible somatic lesions. The study's subjects selected during 2000–2004 from the patients admitted and investigated for neurosurgical conditions; they were divided into two subgroups, based on whether the organic lesions were or were not present (the independent variable). The exclusion criterion was a lesion due to external causes. Statistically meaningful there are seven types of Ego profiles, in relation with the lesion: the archaic ego [0 –], the inhibited ego [– +], the adaptive ego [– –], the narcissist ego [+ +], the identified ego [+/– 0], the fugitive ego [+/– –] and the possessed ego [0 +]. The nexus in the destiny's analysis description highlights the dialectic between the Ego's functions and the drived dangers when facing the demands of the concrete reality.